2019
DOI: 10.1038/s41598-018-36708-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the synthesis method on the catalytic activity of mayenite for the oxidation of gas-phase trichloroethylene

Abstract: Catalytic oxidation of trichloroethylene (TCE) in heterogeneous phase (gas-solid) is an effective strategy for the conversion of this pollutant in less harmful compounds, namely CO2, CO and HCl. In this work, we have studied the use of mayenite, a cost-effective material, as an active catalyst for the TCE conversion. In particular, we have assessed the influence of the mayenite synthesis method (hydrothermal, sol-gel and ceramic) on the reaction performance. The materials have been characterized by different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…As reported in previous works, the deactivation mechanism of mayenite catalyst is related with the displacement of active oxygen species by chloride ions [19,20,24,25]. In particular, the formation of HCl during the reaction caused a partial irreversible substitution of the anionic oxygen species (O x x− ) by chloride ions forming chloromayenite [19,22], with consequent deactivation of the catalyst. It is observed that the presence of iron in mayenite modifies this mechanism, probably because the Fe species catalyze the interaction of the atmospheric O 2 to form O 2− and O 2 2− , making reversible the substitution of chloride ions by oxygen and avoiding or diminishing the formation of chloromayenite.…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…As reported in previous works, the deactivation mechanism of mayenite catalyst is related with the displacement of active oxygen species by chloride ions [19,20,24,25]. In particular, the formation of HCl during the reaction caused a partial irreversible substitution of the anionic oxygen species (O x x− ) by chloride ions forming chloromayenite [19,22], with consequent deactivation of the catalyst. It is observed that the presence of iron in mayenite modifies this mechanism, probably because the Fe species catalyze the interaction of the atmospheric O 2 to form O 2− and O 2 2− , making reversible the substitution of chloride ions by oxygen and avoiding or diminishing the formation of chloromayenite.…”
Section: Resultsmentioning
confidence: 67%
“…Similar results were obtained in the XPS analysis of the samples after reaction (see Supplementary Materials). This does not occur with pure mayenite [19,22], demonstrating that the redox properties of iron catalyze the regeneration of anionic oxygen by the O 2 present in the gas feed and avoid the irreversible chlorine poisoning of mayenite. These results clearly show that the presence of well-dispersed iron on the mayenite surface improves the redox properties of the mayenite together with its stability, due to the ability of iron to catalyse the regeneration of the anionic oxygen responsible for TCE oxidation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Solsona and coworkers employed PMMA as a soft templating agent during catalyst preparation for increasing their surface area, thus improving the oxidation yield of propane [17]. In a previous work, we reported the influence of the synthesis method on mayenite activity for the trichloroethylene (TCE) oxidation [18]. In particular, hydrothermal, ceramic, and sol-gel routes were employed for the synthesis of the mayenite and we found that the hydrothermal method yielded the material with the best catalytic performances due to an optimum combination of surface area and redox properties.…”
Section: Introductionmentioning
confidence: 99%